Perancangan Ui/Ux Sistem Penjualan Sepeda Motor Yamaha Dengan Metode Prototyping Berbasis Website Pada PT Alfa Scorpii Gatot Subroto Medan - Shafhany, Tanwinna; Heni Wulandari; Sri Wahyuni (Jurnal Mahajana Informasi, 2024)
In the era of technological development, this study aims to design a user interface (UI) and user experience (UX) for a website-based motorcycle sales system. The qualitative research method used includes interviews with the marketing and operational teams of PT Alfa Scorpii Gatot Subroto Medan. The results of the study show that the design of a website-based system designed using Figma tools and prototype models. Provides user experience, makes it easier to access promotional information, and increases transaction efficiency. In conclusion, this technology-based Ui/Ux design is expected to help PT Alfa Scorpii Gatot Subroto Medan in increasing competitiveness and ease of understanding products.